Imagination movers [videorecording (DVD)] - Calio, Wendy; Collins, Rich; Durbin, Scott; Poche, David (Distributed by Walt Disney Studios Home Entertainment, 2009)
A hip cast entertains, engages, and develops kids' problem-solving skills. Encourages kids to think outside the box and come up with creative solutions to everyday problems.